DEREKONSTRUKSI KOMUNIKASI SOSIAL KESETARAAN GENDER: DALAM SISTEM BUDAYA PATRIARKI DI INDONESIA - Nurul Azizah (Maddah : Jurnal Komunikasi dan Konseling Islam, 2023)
Conventionally, the social construction of a gender equality society is able to increase awareness of education in a patriarchal culture in Indonesia. The construction of gender equality and gender justice is carried out by people who have concern for the role and progress of women in particular and society in the field of education. Top down affirmations are carried out by various gender equality actions and movements. Women who are the object of the equality movement, to increase gender awareness and justice in the field of education. Along with the times and in the era of digitalization as it is today, it is able to transform the paradigm of women’s thinking. They take an active part in real development through education. Despite going through various challenges and obstacles due to being in a patriarchal culture, where the level of women is lower than that of men. This paper shows that gender equality in education and patriarchal culture, theoretically factual challenges in increasing gender equality, efforts to increase women’s awareness of the importance of education, implementation of gender equality in education in the social context of society. This paper suggests need to provide access and opportunities for women, public policies that are gender-biased oriented, involve women’s participation, so as to be able to provide a just principle of benefit for women, one of which is through education by providing sufficient access to women